Catalysis of concerted reactions by antibodies: the Claisen rearrangement. - Hilvert, D (1988)
Monoclonal antibodies were prepared against a transition state analog inhibitor of chorismate mutase (EC 5.4.99.5). One of the antibodies catalyzes the rearrangement of chorismate to prephenate with rate accelerations of more than 2 orders of magnitude compared to the uncatalyzed reaction. Saturation kinetics were observed, and at 25 degrees C the values of kcat and Km were 1.2 X 10(-3) s-1 and 5.1 X 10(-5) M respectively. The transition state analog was shown to be a competitive inhibitor of the reaction with Ki equal to 0.6 microM. These results demonstrate the feasibility of using rationally designed immunogens to generate antibodies that catalyze concerted reactions.